FRI0382 EFFECTS OF GENICULAR NERVE BLOCK IN PATIENTS WITH KNEE OSTEOARTHRITIS WHO HAVE NEUROPATHIC OR NOCICEPTIVE PAIN. (13th June 2020) - Tas, B.; Akpinar, P.; Aktas, I.; Unlu Ozkan, F.; Kurucu, I. B.
Abstract : Background: Genicular nerve block (GNB) is a safe and effective therapeutic procedure for intractable pain associated with chronic knee osteoarthritis (OA)(1). There is increasing support for the neuropathic component to the knee OA pain. Investigators proposed that targeting treatment to the underlying pain mechanism can improve pain management in knee OA (2). There is a debate on injectable solutions used in nerve blocks (3). Objectives: To investigate the analgesic and functional effects of USG-guided GNB in patients with chronic knee OA (with/without neuropathic pain) and to evaluate the efficacy of the anesthetic and non-anesthetic solutions used. Methods: Ninety patients with chronic knee OA between the ages of 50-80 were divided into two groups with and without neuropathic pain according to painDETECT questionnaire (4). The groups were randomized into three subgroups to either the lidocaine group (n=30) or dextrose group (n=29) or saline solutions (n=31). After the ultrasound-guided GNB, quadriceps isometric strengthening exercises and cryotherapy were recommended to the patients. Visual analog scale (VAS), Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and Lequesne-algofunctional Index were assessed at baseline and at 1 week, 1 and 3 months later after the procedure. Results: Statistically significant improvement was observed in all groups with or without neuropathic pain according to VAS values at the 1 st week, 1 st month and 3 rd month compared to baseline (p<0.05). Statistically significant improvement was observed in all groups with neuropathic pain according to painDETECT values at the 1 st week, 1 st month and 3 rd month compared to baseline (p<0.05). There was a statistically significant improvement in the groups without neuropathic pain which received dextrose and saline solutions, according to painDETECT values, but not in the group which received lidocain at the 1 st week, 1 st month and 3 rd month compared to baseline (p>0.05). There was a statistically significant improvement in all groups with or without neuropathic pain according to WOMAC and Lequesne total scores at the 1 st week, 1 st month and 3 rd month compared to baseline (p<0.05). Conclusion: We conclude that in patients with chronic knee OA (with/without neuropathic pain), the use of GNB with USG is an analgesic method which provides short to medium term analgesia and functional recovery and has no serious side effects. The lack of significant difference between the anesthetic and non-anesthetic solutions used in the GNB suggests that this may be a central effect rather than a symptom of peripheral nerve dysfunction. It suggests that injection may have an indirect effect through nociceptive processing and changes in neuroplastic mechanisms in the brain. In addition, we can say that regular exercise program contributes to improved physical function with the decrease in pain. References: [ 1]Kim DH et al. Ultrasound-guided genicular nerve block for knee osteoarthritis: a double-blind, randomized controlled trial of local anesthetic alone or in combination with corticosteroid. Pain Physician 2018;21:41-51. [2 ]Thakur M et.al. Osteoarthritis pain: nociceptive or neuropathic?. Nat Rev Rheumatol 2014:10(6):374. [3 ]Lam SKH et al. Transition from deep regional blocks toward deep nerve hydrodissection in the upper body and torso: method description and results from a retrospective chart review. BioMed Research International Volume 2017;7920438. [4 ]Hochman JR et al. Neuropathic pain symptoms in a community knee OA cohort. Osteoarthritis Cartilage. 2011 Jun;19(6):647-54. Disclosure of Interests: None declared